Pengaruh Disiplin Kerja dan Budaya Kerja Organisasi yang Dimediasi Motivasi Kerja terhadap Kepuasan Kerja Karyawan di PT. Kelola Jasa Artha Semarang - Yusuf Ehza Putra; Qristin Violinda; Bayu Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of work discipline and organizational culture on employee job satisfaction at PT. Kelola Jasa Artha Semarang, with work motivation as a mediating variable. Work discipline and organizational culture are considered important factors influencing employee motivation and job satisfaction. This study used a quantitative approach with a survey method involving 105 respondents working at PT. Kelola Jasa Artha Semarang. Data were collected through questionnaires and analyzed using multiple linear regression and path analysis to examine the relationships between variables. The results indicate that work discipline has a positive and significant effect on work motivation, organizational culture has a positive effect on work motivation, and work motivation has a significant effect on job satisfaction. Furthermore, work motivation has been shown to mediate the influence of work discipline and organizational culture on employee job satisfaction. Therefore, improving work discipline and a supportive organizational culture can increase work motivation, which ultimately leads to increased employee job satisfaction within the company.